Pengaruh Kompetensi dan Komitmen Organisasional Terhadap Kinerja Guru dan Pegawai pada SMP dan SMA Muhammadiyah 2 Singaraja - Hidayat, Sarif; Heryanda, Komang Krisna (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This research aims to examine the effect of competence and organizational commitment on the performance of teachers and employees at SMP and SMA Muhammadiyah 2 Singaraja, namely partially and simultaneously. The research design used in this research is quantitative causal. The subjects in this study were teachers and employees at SMP and SMA Muhammadiyah 2 Singaraja while the objects of this study were competence, organizational commitment and employee performance. The research population used was 37 employees. The data collected by results of questionnaires and interviews were then analyzed by multiple regression analysis. The results of this study indicate (1) competence and organizational commitment have a significant effect on employee performance, (2) competence has a positive effect on employee performance, and (3) organizational commitment has a positive effect on employee performance.